IDENTIFIKASI DAN UJI ANTI KANKER TABLET EKSTRAK DAUN PALIASA (KLEINHOVIA HOSPITA LINN) SECARA MTT ASSAY - Yetri Elisya; Junaedi Junaedi; Maratu Saleha (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Indonesia has several plants that can be developed into cancer drugs. This study aims to make tablet preparations containing Paliasa leaf extract to produce pharmaceutical preparations for anticancer use. Paliasa leaves were extracted by maceration using 70% alcohol; then, the tablets were made using the wet granulation method. The extract obtained from 2,207 kg of dried simplicia paliasa leaves was 542 grams, with a yield of 24.56%. The flavonoid content in the extract was 1.79%, and the tablet was 0.75%. There are active compounds, namely 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl, a powerful antioxidant blend, hexadecanoic acid, or palmitic acid functions as an antibacterial and antioxidant, and kaempferol is one of the compounds, which has potential as an anticancer. The identification of extracts and tablets of paliasa leaf (Kleinhovia hospital Linn) resulted in IC50 above > 30 ppm in the inactive category, so the bioactivity of paliasa leaf extract was studied further fractionation.